Contribuições da coordenação pedagógica para formação continuada de professores do ensino fundamental I na área de matemática - Alves, Andréa Ramires (2013)
The theme that the title of this dissertation, "Contributions of the coordinating education for continuing education of elementary school teachers in the area of Mathematics I," was born of concerns that emerged during the life experience and academic and professional researcher. In his role as educational coordinator, the author observed the transformation of his vision, his repertoire of practical and theoretical your search. Thus, the problem is investigated here as coordinating education can contribute to continuing education, in-service teachers of elementary school in the area of mathematics? To this end, this research aims to contribute to the practice and teacher training. Provide insight to the teacher of elementary school multipurpose area of mathematics in their daily routine, through the work of the pedagogical coordination via HTPC (Hours of Work Educational Collective). This time, it is expected that the study will contribute to the debate on scientific knowledge in the area of education. The research took place in two state schools of São Paulo, the same board of education in the city of Guarulhos. The study is guided by the principles of qualitative research, with some contribution from quantitative research. For data collection, questionnaires were elaborated and developed structured interviews with school teachers surveyed; semistructured interview with a pedagogical coordinator at another school in the same board of education; documentary and bibliographic research, the theories of authors who collaborate to discussion of the subject, such as: Abramowicz, Alarcão, Brito, Brousseau, Canary Chizzotti, Dowbor, Feldman, Franco, Freire, Fusari, Garrido, Gatti, Imbernon, Laville, Mizukami, Nóvoa, Parra, Perrenoud, Placco, Tardif, Vasconcelos , among others. The results show that it is possible to contribute to the pedagogical coordinator continuing education of teachers in the area of Mathematics. The research also hints at the factors and actions that favored the formation or did not contribute to the training process of teachers. Presents proposals for possible action against the pedagogical coordinator training in mathematics, reflecting a significant learning for students